Banking on Protected Areas : Promoting Sustainable Protected Area Tourism to Benefit Local Economies - World Bank (World Bank, Washington, DC, 2021)
Protected areas are key to any global effort to conserve biodiversity. While governments see protected areas as key to addressing biodiversity loss, they are often overlooked in economic development plans and recovery strategies. One reason for this is because data gaps make it difficult to demonstrate protected area tourism’s far-reaching stimuli to national and local economies, especially in developing countries. The study therefore quantifies the impacts of protected area tourism on local economies to show that protected areas promote conservation and development. It makes the case that the promotion of sustainable tourism in protected areas should be actively included in COVID-19 economic recovery plans, an investment that would provide jobs and support economic development while also protecting biodiversity.